SUPPORT TO AGRICULTURE AND RURAL DEVELOPMENT IN FUNCTION OF DECREASING POVERTY IN SERBIA - Popović, Vesna; Milovanović, Milos; Tomić, Danilo (Economics of Agriculture, 2008)
Around 45% of total population lives in rural areas, which cover almost three quarters of the country. Multiannual migration of population on relation rural-urban areas, followed by not fully appropriate social and rural policy, led to significant depopulation of rural areas. Multiannual practice of not investing in development of rural infrastructure and other aspects of rural living (strengthening of social and educational component of living in rural areas, development of rural economy not necessarily linked to agriculture, environmental protection…) made from rural areas parts of countryside with limited non-agricultural employment possibilities and providing permanent source of descent living, limited educational possibilities, insufficiently developed social aspects of everyday life and by all of these – unattractive areas for living of all residents and especially, young generations as key stakeholders in development of rural areas. Active role of Government and budget, Ministry in charge among other responsible institutions, for programming and financing measures of support to sustainable agricultural and rural development can play most important role in decreasing rural poverty.